Analisis SWOT Program Ekstrakurikuler di SDN 068 Sindanglaya - Annisa Dwi Hamdani; Annisa Laela Putri; Melani Khalimatu; Syifa Dilla Khansa; Agus Mulyana (Jurnal Bintang Pendidikan Indonesia, 2024)
The aim of this research is to find out how extracurriculars are implemented at SD Negeri 068 Sindanglaya and analyze the strengths, weaknesses, opportunities and threats of the school's extracurriculars. The method used in this research is descriptive qualitative method. The research we conducted was field research in which school principals and extracurricular coaches were the subjects. Data collection was taken by means of observation, interviews and documentation. After conducting research, the results showed that extracurricular activities at SD Negeri 068 Sindanglaya had strengths, namely, teachers were actively involved as coaches and trainers supported by external trainers who were experts in their fields and increased students' interests and talents. Meanwhile, the weaknesses are limited time, budget and facilities. The opportunities obtained include cultivating good behavior and character, developing personal potential, skills and interests, and providing opportunities to become outstanding students. However, in its implementation there are also several threats, including a lack of support from parents or guardians of students and a lack of motivation for students to take part in extracurricular activities.